2009
DOI: 10.1111/j.1600-0404.1990.tb00928.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis and other immunologic diseases

Abstract: A characteristic feature of immunologic diseases is their association with each other. For multiple sclerosis (MS), several retrospective studies reported increased as well as expected coincidence rates with other immunologic diseases. We conducted a prospective case-control study of MS patients and healthy volunteers and found 13/101 MS patients and 2/97 controls with such diseases (P = 0.009, chi-square test), as well as 47/88 MS patients versus 31/95 controls with a variety of circulating autoantibodies (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 41 publications
3
54
0
3
Order By: Relevance
“…Although this was similar to the frequency of 23–33% identified by many studies, [3][4], [9], [15][16], [22] elevated ANA has also been detected in higher (47–81%) [12], [18], [22] and lower (3%–19%) frequency in MS patients [5], [19][21], [23] in additional literature. It is important to note that ANA has been detected at a frequency of 32% at 1∶40 dilution, 13% at 1∶80, 5% at 1∶160 and in 3% at 1∶320 in healthy individuals.…”
Section: Discussionsupporting
confidence: 90%
“…Although this was similar to the frequency of 23–33% identified by many studies, [3][4], [9], [15][16], [22] elevated ANA has also been detected in higher (47–81%) [12], [18], [22] and lower (3%–19%) frequency in MS patients [5], [19][21], [23] in additional literature. It is important to note that ANA has been detected at a frequency of 32% at 1∶40 dilution, 13% at 1∶80, 5% at 1∶160 and in 3% at 1∶320 in healthy individuals.…”
Section: Discussionsupporting
confidence: 90%
“…Prior studies were inconsistent with respect to a possible increased risk of AIT in the MS population [2,4,29]. Among studies which were population-based, one did not find an increased risk, one with small sample sizes found an increased risk of Graves’ disease but not Hashimoto’s disease, while the Taiwanese study found a threefold increased risk of hypothyroidism in MS [4,5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated the occurrence of autoimmune thyroid disease (AIT) in the multiple sclerosis (MS) population, reporting prevalences ranging from 0.92 to 13.9% [1,2]. Some of these studies suggested that AIT is more common in individuals with MS as compared to the findings expected for the general population [3,4,5]; however, most of these studies did not use contemporaneous control groups.…”
Section: Introductionmentioning
confidence: 99%
“…2 Bir organa spesifik olsun veya olmasın, MS hastalarında birtakım otoantikorların normal populasyona göre daha fazla bulunduğu görülmüştür. 3 Otoimmün tiroiditin ve tiroid fonksiyon bozukluklarının MS hastalarında kontrol grubuna göre yüksek bulunduğu daha önceki çalışmalarda gösterilmiştir. [4][5][6] Bu çalışmada MS hastalarında tiroid otoantikor düzeyleri ve otoimmün tiroiditin normal sağ-lıklı bireylerden farklı olup olmadığı ve interferon tedavisi sonrasında tedavi öncesi mevcut olmayan bir tiroid otoimmünitesinin ilaç etkisi ile gelişip gelişmediğinin belirlenmesi amaçlanmıştır.…”
unclassified